O uniwerbizmach z formantem „-ka” - Nowicka, Beata (Studia Rossica Posnaniensia, 2010)
This article is devoted to the study of Russian derivatives with suffix -к(а) which are the result of univerbisation, i.e. transformation of complex nominal expression into a single word with the same meaning, cf. камералка ← камеральная обработка, канадка ← канадская стрижка, секретка ← секретное противоугонное устройство. The analysis demonstrated here is based on the material of the latest Russian lexicon